Synchronising Positive Law and Islamic Law Within a Justice Concept in Concurrent Elections 2024: From The Philosophical Perspective of Islamic Law - Mahir, Mahir (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Concurrent elections should not be injured by dissenting interpretations of Islamic Law in terms of its contextual connection to Positive Law. This research aims to delve into the connection between the norms of Islam and politics in Indonesia and the measures taken to bring about the harmony of religious norms within the political system of law in Indonesia. With a normative-descriptive approach, this legal research discovered that the legal objective is not restricted to justice, but it also takes into account legal certainty and merit. The discourse on justice often refers to two thoughts. John Rawls and Jürgen Habermas, within the scope of critical philosophy developed by Kant, attempted to seek the primary principles underlying social life. Concurrent elections 2024 in Indonesia refer to direct, universal, free, secret, genuine, and just principles. These principles serve as the basis for justice enforcement, especially in the fulfilment of the political rights of the citizens. The justice principle builds the harmonization of the norms that underlie elections with Islamic Law as the core soul of the elections. Participation in elections is understood as the exercise of the norms of Islamic law with the frameworks aiming to bring about the merit of the people as a whole. How do the principles of justice in the principles of elections intertwine with the principle of justice in Islamic law? Keywords: Harmonization, justice, concurrent elections, the philosophy of Islamic Law